Pengaruh Penggunaan Model Pembelajaran Learning Cycle 5E Terhadap Minat dan Hasil Belajar Biologi Siswa SMA - Elsa Mansyur (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
In connection with the biology learning process, it is known that the activities of some students are less active when the teaching and learning process takes place. Most students only receive information directly from the teacher. The class situation looks very formal and students don't get the opportunity to respond to the material presented, either by asking questions or by other activities, so they don't train students' thinking skills. Thus the objectives to be achieved in this study are: (1) To find out interest and learning outcomes in biology before and after the 5E Learning Cycle learning model is applied (2) to find out whether there is an effect of using the 5E Learning Cycle learning model on interest and learning outcomes in Biology . This type of research is experimental research. Experimental research (Experimental Research) using a quasi-experimental design with the type of One Group Pretest Posttest Design. Based on the results of the research that has been discussed, it can be concluded as follows: Interest in learning biology before being given treatment is in the medium category. After learning by using the 5E learning cycle learning model is in the high category. Student biology learning outcomes before being given treatment were in the low category, after being given treatment were in the high category. There is an effect of using the 5E learning cycle learning model on the interest and learning outcomes of class XI UPT SMA Negeri 1 Palopo.